Sistem Pendukung Keputusan Untuk Pendistribusian Beras Masyarakat Miskin Menggunakan Logika Fuzzy Sugeno - Febiola, Dwi Suci; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Poor people’s rice program or commonly known as Raskin is one of the government’s effort to reduce the burden of spending on the poor and as a social protection. To prevent mistakes in determining Raskin recipients and to avoid cheating by certain parties a system is needed. Decision support systems can overcome this problem, the system can support decision making Raskin recipients based on the criteria specified, so that the calculation is more accurate then the fuzzy logic implementation is used in decision making. The use of fuzzy logic in this system is based on the advantages of fuzzy logic, namely fuzzy logic tolerates incorrect data, fuzzy logic can model functions that are not linear, and fuzzy logic is based on natural language that is easy to understand. The fuzzy logic method used in this study is the Mamdani Method and Sugeno Method, which of the two methods will be compared to the best method by calculating the accuracy and error rate of the two methods. Keywords: Raskin, Decision support systems, Fuzzy logic, Recipient